Penggunaan Gel Lidah Buaya (Aloe vera) Sebagai Koagulan Alami Dalam Penjernihan Air Sumur Di Desa Sausu Tambu Kecamatan Sausu - Mujariah, Mujariah; Abram, Paulus Hengky; Jura, Minarni Rama (Jurnal Akademika Kimia, 2016)
Research on the use of aloe vera gel (aloe vera) as a natural coagulant in water purification village wells Sausu Tambu has been done. This study aims to determine whether aloe vera gel can be used as a natural coagulant and determine the optimum ratio of aloe vera gel in water (V/V) which is used in the purification of water wells in the village Sausu Tambu. Research was conducted on the water sample preparation, natural production of aloe vera gel, water treatment and analysis of water quality parameters, namely turbidity, hardness, color, pH and temperature. The results showed that aloe vera gel can be used as a coagulant to purify the water with an optimum ratio of 0.3 mL aloe vera gel in 500 mL water sample. Aloe vera gel can reduce 72.22% of turbidity, 63.48% hardness, 68.62% color with a pH of 5.5 and a temperature of 30 oC. It can be concluded that the aloe vera gel has the ability as a coagulant to purify water.